1995
DOI: 10.1073/pnas.92.14.6294
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal enterotoxins bind H-2Db molecules on macrophages.

Abstract: We screened a panel of monoclonal antibodies against selected macrophage cell surface molecules for their ability to inhibit enterotoxin binding to major histocompatibility complex class II-negative C2D (H-2b) macrophages. Two monoclonal antibodies, HB36 and TIB126, that are specific for the a2 domain of major histocompatibility complex class I, blocked staphylococcal enterotoxins A and B (SEA and SEB, respectively) binding to C2D macrophages in a specific and concentration-dependent manner. Inhibitory activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Immunoprecipitation data suggest an association of LINE-1 product with MHC class I or MHC Class I-like molecules since both 45-and 12-kDa proteins, immunoprecipitated by the Ab d /LINE-1 mAb, were removed from lymphoid cell lysates by preclearing with anti-b2m serum. Such associations with MHC class I molecules have been described for insulin receptor (Chvatchko et al, 1983;Due et al, 1986) and staphylococcal enterotoxin superantigens (Beharka et al, 1995). The MHC fold can perform other functions in addition to presentation of antigenic peptides to T cells.…”
Section: Discussionmentioning
confidence: 82%
“…Immunoprecipitation data suggest an association of LINE-1 product with MHC class I or MHC Class I-like molecules since both 45-and 12-kDa proteins, immunoprecipitated by the Ab d /LINE-1 mAb, were removed from lymphoid cell lysates by preclearing with anti-b2m serum. Such associations with MHC class I molecules have been described for insulin receptor (Chvatchko et al, 1983;Due et al, 1986) and staphylococcal enterotoxin superantigens (Beharka et al, 1995). The MHC fold can perform other functions in addition to presentation of antigenic peptides to T cells.…”
Section: Discussionmentioning
confidence: 82%
“…Immunoinflammatory responses are orchestrated by cytokines, and T-cell mitogens and superantigens are potent stimuli for cytokine production from T cells, monocytes, and macrophages (2,3). In CF there is a misdirected or dysregulated response, since there is a chronic and exuberant immunoinflammatory response without clearance of the pathogen.…”
mentioning
confidence: 99%
“…This is a reproducible process that occurs with cells not only of the H-2 b haplotype [15] but also with cells expressing the H-2 k haplotype; the latter being a slightly higher-affinity binding than that seen for H-2D b (10 -5 to 10 -6 M vs. 10 -6 to 10 -7 M). It is curious that others have not readily detected binding to H-2K k or D k .…”
Section: Discussionmentioning
confidence: 90%
“…(2) We demonstrated that superantigens can bind to MHCI molecules other than H-2D b . We had previously shown that SEA had micromolar affinity for MHCII -/-macrophages [14], that antibodies specific for H-2D b could block superantigen binding to macrophages [15] and that H-2D b could directly bind SEA [Wright and Chapes, unpublished results], however, it was not clear if superantigen binding to D b was unique or a phenomenon that occurred with other MHCI molecules. Our data suggest that the MHCI-superantigen interaction may occur more frequently in nature than has been previously acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation